PENGARUH ELECTRONIC WORD-OF-MOUTH DAN RATING KONSUMEN DI SITUS FEMALE DAILY TERHADAP MINAT BELI PRODUK DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING (Studi pada Pengunjung Female Daily di Kota Semarang - Dewima Rima Aini; Sri Rahayu Tri Astuti (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to analyze the factors that influence trust and implications for the purchasing intention in Female Daily website in Semarang Regency. This study consisted of two independent variables, one intervening variable, and one dependent variable. The independent variables in this study are electronic word-of-mouth and consumer rating. The intervening variable in this study is trust, while the dependent variable in this study is the purchase intention. The population in this study were visiters of Female Daily situs in Semarang County. The sample used was 128 respondents. The data collection technique is carried out using questionnaires. The data analysis used in this study is StructuralEquation Modeling (SEM) which is operated through the AMOS 22.0 program. The results of this study show that electronic word-of-mouth and consumer rating have positive impact on trust. Electronic word-of-mouth and consumer rating have positive impact on purchase intention, and trust have positive impact on purchase inten